The prognostic value of right ventricular free wall and global longitudinal strain in the general population. (3rd October 2022) - Espersen, C; Hauser, R; Skaarup, K G; Lassen, M C H; Johansen, N D; Olsen, F J; Jensen, G; Schnohr, P; Moegelvang, R; Biering-Soerensen, T
Abstract: Background: Right ventricular free wall (RVFWLS) and global longitudinal strain (RV4CLS) have been shown to be prognostic of adverse events in various patient groups including patients with heart failure (HF). Purpose: We sought to investigate the prognostic value of RVFWLS and RV4CLS for the development of incident HF in participants from the general population. Methods: Participants from the echocardiographic substudy of the 5th Copenhagen City Heart Study (2011–2015) without chronic ischemic heart disease or heart failure at baseline were included. RVFWLS and RV4CLS were obtained using two-dimensional speckle-tracking echocardiography from the RV-focused apical 4-chamber view. The primary endpoint was incident HF. Results: Among 2, 804 participants (mean age 55, 42% male), 45 (1.6%) developed HF during a median follow-up of 5.4 years (IQR 4.5–6.3). Both RVFWLS and RV4CLS were associated with increased risk of HF in univariable cox regression analysis (HR 1.07, 95% confidence interval (CI) 1.02–1.12, p=0.003, and HR 1.21, 95% CI 1.11–1.31, p<0.001, respectively). Upon adjustment for age, sex, hypertension, diabetes and body mass index (BMI), both RVFWLS and RV4CLS remained associated with increased risk of incident HF (HR 1.05, 95% CI 1.00–1.11, p=0.038 and HR 1.13, 95% CI 1.04–1.22, p=0.004, respectively). Conclusion: RVFWLS and RV4CLS were associated with an increased risk of incident HF in participants from the general population independent of age, sex, hypertension, diabetes and BMI. Funding Acknowledgement: Type of funding sources: None.